Effect of scraped-surface tube cooler temperatures on the physical properties of palm oil margarine - Miskandar, M. S.; Che Man, Y. B.; Yusoff, M. S. A.; Abdul Rahman, R. (Wiley, 2002)
The effects of scraped‐surface tube cooler temperatures on the isothermal solid fat content (SFC) of palm oil margarine during processing and on margarine consistency (yield value, g/cm2), SFC, and polymorphic changes in storage were studied. SFC was measured in the mixing tank after leaving the tube cooler and the pin worker. The SFC at the tube cooler exit was proportional to the amount of cooling; a higher SFC was produced by more extreme cooling treatment. The SFC of all margarines were reduced in the pin worker, and the reduction was related to the initial SFC profile of palm oil. Margarine samples were stored at 28°C for 28 d and tested daily. Margarine processed at 25°C in the tube cooler had the highest consistency and the least change in SFC, but by the second week crystals had transformed into the β form. Uniform product consistency and SFC were observed in margarines processed at 20 and 15°C. These margarines retained the β′ crystal form for 3 and 4 wk, respectively. The best palm oil margarine was obtained with a tube cooler temperature of 15°C and a residence time of 1.8 min.